2013
DOI: 10.1037/a0032197
|View full text |Cite
|
Sign up to set email alerts
|

Well-being of individuals with late-deafness.

Abstract: Perceived adaptation to disability and perceived severity of disability acted as direct predictors of psychological well-being, and as indirect predictors through their relationship with coping. Implications for the process of adaptation and counseling for individuals with acquired hearing loss are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…One study examined the relationships between disability factors and psychosocial outcomes in a sample of individuals with acquired hearing loss, specifically late deafness (loss between 12 and 65 years of age). The author reported that age of onset of hearing loss only correlated with one variable, the Hearing Handicap Inventory for Adults total score, indicating that, as age of onset increased, so did perceived severity of disability (Meyer & Kashubeck-West, 2013). Our study did not reveal an association between the time of onset of hearing loss and the degree of self-reported hearing handicap in adulthood.…”
Section: Time Of Onset Of Hearing Losscontrasting
confidence: 77%
“…One study examined the relationships between disability factors and psychosocial outcomes in a sample of individuals with acquired hearing loss, specifically late deafness (loss between 12 and 65 years of age). The author reported that age of onset of hearing loss only correlated with one variable, the Hearing Handicap Inventory for Adults total score, indicating that, as age of onset increased, so did perceived severity of disability (Meyer & Kashubeck-West, 2013). Our study did not reveal an association between the time of onset of hearing loss and the degree of self-reported hearing handicap in adulthood.…”
Section: Time Of Onset Of Hearing Losscontrasting
confidence: 77%
“…Turning now to the difference between pre- and post-lingually deafened subjects, our results showed that the post-lingually deafened had the lowest self-esteem of all CI users. For some reason, they were most affected by the negative, devastating effects–the “trauma” as a number of our subjects called it–of profound or total loss of hearing [ 19 , 44 – 45 , 48 , 81 ]. Therefore, this group of patients should be a priority for professional psycho-educational, psychological, and psychotherapeutic interventions aimed at maintaining their self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…As for marriage and partnerships, deaf people generally have greater difficulty establishing intimacy compared to hearing persons [ 7 ]. At the same time, for people with post-lingual deafness, hearing loss and its consequences often have negative effects on existing relationships [ 6 , 19 , 45 , 47 – 48 ]. At a more general level, recent studies in the wider population have shown that good quality relationships are conducive to self-esteem, and higher self-esteem is also likely to be responsible for creating closer relationships [ 10 , 88 – 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychsocial consequenses of HI, such as lowered QoL, cannotbe predicted from audiometric data alone. 33 Helvik, A. S., et al, 2006 [ 52 ] Cross sectional PGWB Mixed, mean duration of the HI was 15.1 years 343 (55% male) 21–94 years, mean age 69 years Not specified Mean threshold of hearing for the total sample was 43.0 dB Not specified Psychological well-being was associated with activity limitation and participation restriction, but not with the degree of HL and use of communication strategies 28 Lotfi, Y., et al, 2009 [ 48 ] Cross sectional/Longitudinal HHIE First time users 207 (71% male) ˃60 years, meanage 73.01 years Not specified Moderate HL: 56–70 dB Profound HL: 71–90 dB Before HA fitting and after 3 months Significant improvement in QoL after HA fitting 19 Meyer, J. M. and S. Kashubeck-West, 2013 [ 55 ] Cross sectional HHIA and The meassureof psychological well-being (generic) Not specified 277 (25% male) 18–65 years Mean age49 years Not specified Not specified Not specified Relationship between perceived severity and perceived disability acted as direct predictors to well-being and as a indirect predictors through their relationship with coping. No significant association between QoL and HL 30 Miyakita, T., et al, 2002 [ 54 ] Cross sectional Generic, LISZ, 13 questions about QoL Not specified 210 retired workers, gender not specified 56–65 years, mean age 60.6 years Not specified Not specified Not specified Hearing disabillities was associated with deteriorationin QoL.…”
Section: Methodsmentioning
confidence: 99%